Comparing the “value of information services” for providers and vulnerable patrons: a mixed-methods study with academic libraries and students with disabilities - Potnis, Devendra; Mallary, Kevin (Information Research an international electronic journal, 2023)
Introduction. This multi-year, mixed-methods study compares (a) the reasons administrators and librarians of academic libraries invest in assistive technology for delivering information services to students with disabilities, with (b) the benefits that influence these students’ intention to use AT. Method. In the first phase, 50 library administrators and 22 librarians from 186 public universities across the US shared their top-three reasons for investing in assistive technology through a qualitative survey. In the second phase, 322 students with disabilities from the same institutions completed a quantitative survey, in which respondents shared individual-level benefits that influence their intention to use assistive technology. Analysis. We utilised thematic analysis and structural equation modelling to analyse data in the first and second phases, respectively. Results. Three individual, three organisational, and three societal benefits prompt academic libraries’ investment in assistive technology. However, only two individual benefits – increasing information literacy and completing academic tasks – significantly influence the intention of students with disabilities to use the technology. In addition, neither academic libraries nor students, perceive the technology to be valuable for enhancing autonomy and the self (i.e., self-esteem, self-efficacy, and self-image) of students with disabilities. Conclusion. Implications for academic libraries that provide information services to students with disabilities are discussed at the end.